The Fundamental Role Of Movement Skills In Optimizing Children's Motor And Cognitive Development: Systematic Literature Review - Barikah, Khasanatul; Adi, Sapto; Ashfiya’, Muhammad Ashfal; Puspa, Sukma Aura (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
Fundamental Movement Skills (FMS) are an important foundation in the motor development of elementary school-age children and play a role in supporting the participation of physical activities throughout life. This study aims to analyze the effectiveness of FMS intervention in improving Fundamental Movement Skills in PJOK learning in elementary schools. The research method uses a literature study by examining five relevant scientific articles. The analysis was carried out in a descriptive-comparative manner by comparing the research methods, the form of intervention, the variables measured, and the main findings of each study. The results of the study show that FMS interventions carried out in a structured and integrated manner in school learning are effective in improving children's Fundamental Movement Skills, especially in locomotor skills and object control skills. Game-based interventions have also been proven to be able to increase students' movement competence and confidence. In addition, intervention programs with a relatively short duration can still have a positive impact if implemented in a focused and systematic manner. Based on these results, it can be concluded that FMS interventions have a strong empirical basis to be applied in PJOK learning in elementary schools to support children's motor development optimally and sustainably.